(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article states that the study of the life and spiritual and scientific heritage of Ibn Sina, provides ample opportunities for the work of people in the field of spirituality, morality, educational education, and those principles such as mutual respect, kindness, hard work, homogeneity and humanism are important in the upbringing of children. In addition to it, he outlined one of the main ideas of Aloma in his natural-scientific, philosophical views on moral issues in his works entitled “Treatise of science ethics”, “Treatise of The Covenant”, “Treatise on the Purification of Ruki”, in which he understood the science of morality as the science of human behavior, character. In his work “Treatise on the Science of Morality”, he provides information on the content and nature of good and bad behavior in the practical activities of a person and the reasons for their occurrence. Keywords: Justice, chastity, honor and integrity, generosity and Bliss, wisdom and ignorance, love and hatred, honest and unclean, purity. Introduction. Thanks to our independence, it was possible to study our centuries-old national values and instill in them progressive thoughts in the direction of spiritual and educational upbringing of young people. The socio-moral education of young people, the formation of their social activity was defined as one of the important tasks of youth policy. He fact that in accordance with this law, the principles on which youth policy will be based are established is a vivid proof of this. Examples of this include caring for young people regardless of national, racial, language, religious affiliation, social status, gender, education, and political affiliation”, “legal and Social Protection of young people”, “supporting youth initiatives, guaranteeing their choice”. In today’s threatening time, ensuring social stability, living peacefully among peoples, working in harmony are important for the spiritual property of all mankind. The role of the spiritual heritage of our great ancestors contributed to this is incomparable. Our President Sh. Mirziyoev noted: “It is known that from the land of our country, which is a crossroads of ancient cultures and civilizations, thousands of scientists, allomas, great thinkers, poets, Saints grew up in the Middle Ages. His valuable heritage in the field of Exact Sciences and religious sciences is the spiritual property of all mankind. One of the main ideas of Ibn Sina in his natural-scientific, philosophical views is the issues of ethics. Ibn Sina glorifies moral qualities and sharply condemns vices. The manifestation of the moral qualities of a person in society, the monotheism of family members built on a mutual moral basis, the mutual moral monotheism of various classes in society are specially covered in the works of Ibn Sina.